The Effect of Internal Audit on Budget Management of Local Government of Rwanda (Global Journal of Management and Business Research, 2018)
This study aimed at investigating the effect of internal audit on budget management of local government of RwandatakingMusanze District as case study. The problem of failing to consolidate transactions and balances of NBAs in financial statements of local government has still persisted. Many local governments have not been examining efficiently the internal audit in budgeting process and execution and this has consequently led to mismanagement; lack of control and less budget execution from their activities or operations. Moreover to prove the general objective, the results of this study was presented in accordance with specific objectives stated by the researcher such as, to analyze the internal audit functions in local government of Rwanda; to assess budget process and execution in local government in Rwanda and to analyze the relationship between internal audit and budget process and execution in Rwanda. Descriptive research design was adopted for this study using both qualitative and quantitative methods of data collection. The studyused a sample of 18 employees of Musanze District office selectedpurposivesampling techniques from a targeted population of 18 employees from department of finance of Musanze district Office. The study used primary data collected from semi-structured questionnaires. Based on the findings of this study, it was found that asset management; management control and staffing management are well used to enhance good budgeting process and execution in local government as it was indicated by 100% of respondents. The budget process and execution in local government is based on budget formulation; budget proposal and dialogue, budget monitoring, budget adjusting, budget control and budget reporting (100%). As significant level is at 0.01 (1%), the p value of 0.000(i.e. 0.0%) is less than 1%. This leads to confirm that there is significant relationship correlation between internal audit and budget process and execution in Musanze district office. As it was recommended that Musanze District should put more efforts in raising more revenue to supplement the government transfers and smoothen the budget execution.
Keywords: internal audit; budget process; executionand local government